Breaking the news? Should digital platforms be required to fund news publishers? - Matthew Lesh (Institute of Economic Affairs (IEA), 2023)
The internet has challenged the traditional news publisher business model by increasing competition for audiences and advertising revenue. Publishers have responded by seeking revenue transfers from the large, profitable digital platforms including Google and Meta's Facebook. But the loser in an economic transformation facing competition is not intrinsically entitled to compensation. The UK government has proposed a system of mandatory negotiation between publishers and platforms, modelled on the Australian government's news media bargaining code. However, such a system would be mistargeted, is built on a false premise, and could have many adverse unintended consequences. Firstly, the major digital platforms are not responsible for the problems faced by news publishers. A broad range of digital content providers and the fall of classifieds advertising has undermined the traditional publisher business model. Google and Meta did not take publishers' money any more than Henry Ford stole from the horse and carriage industry. New technology emerged, consumer preferences changed, and the previous business models fell apart. Secondly, proponents mischaracterise the relationship between news publishers and digital platforms by claiming that the platforms are 'free riding' on journalism. The digital platforms contain news links and snippets. Linking to third-party websites is entirely legal and, in fact, central to the nature of the internet. There is no reason this behaviour should be limited or require payment. In any case, the value of news to digital platforms has been greatly exaggerated. News plays a relatively small part in digital platforms. By contrast, publishers of varying sizes significantly benefit from search and social media. Digital platforms provide access to larger audiences, referring traffic to news sites and driving subscriptions and advertising revenue. Finally, a revenue transfer system could have numerous unintended consequences, such as inhibiting innovation, undermining journalistic quality, and discouraging news on the platforms.
Keywords: 330; Newspaper; Electronic publication; Digital platform; Financing; Press publishing; Online marketing; Regulation; United Kingdom; Zeitung; Elektronische Publikation; Digitale Plattform; Finanzierung; Presseverlag; Online-Marketing; Regulierung; Großbritannien